Time and Concentration-dependent Cytotoxicity of Piperine on Hela Cells - Sri Oktavia; Arni Amir; Fatma Sri Wahyuni; Hasmiwati Hasmiwati (Majalah Kedokteran Andalas)
Piperine, the primary alkaloid of Piper nigrum and Piper longum, is believed to have anticancer properties. Although research on cervical cancer is still in its early stages, piperine's anticancer capabilities have been established in numerous types of cancer and have been shown to target pathways involved in the cell cycle and apoptosis. This study aims to determine how piperine administration time and concentration affect the viability of Hela cells. The MTT method was used to conduct this study. The concentration of piperine utilized was 1,000; 500; 250; 125, and 62.5 µg/mL, and it was administered for 24 and 48 hours. The IC50 values, obtained after incubation for 24 and 48 hours, were 711.21 µg/mL and 419.75 µg/mL, respectively. We may conclude that the viability of HeLa cells is influenced by piperine in a time- and concentration-dependent manner (p<0.05).